2020
DOI: 10.1136/neurintsurg-2020-016851
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular therapy in the distal neurovascular territory: results of a large prospective registry

Abstract: BackgroundThere is a paucity of data regarding mechanical thrombectomy (MT) in distal arterial occlusions (DAO). We aim to evaluate the safety and efficacy of MT in patients with DAO and compare their outcomes with proximal arterial occlusion (PAO) strokes.MethodsThe Trevo Registry was a prospective open-label MT registry including 2008 patients from 76 sites across 12 countries. Patients were categorized into: PAO: intracranial ICA, and MCA–M1; and DAO: MCA–M2, MCA–M3, ACA, and PCA. Baseline and outcome varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Moreover, as less than 50% of the Trevo registry patients met the inclusion criteria for previous RCTs, it represents a unique opportunity to explore new treatment paradigms. 31,32 In conclusion, our study provides favorable data for the generalizability of the safety and efficacy of thrombectomy in the ''real-world'' setting and adds to the growing literature supporting that patients may be safely treated outside the constraints of randomized trials and strict guidelines. Other coauthors: critical revision of manuscript.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, as less than 50% of the Trevo registry patients met the inclusion criteria for previous RCTs, it represents a unique opportunity to explore new treatment paradigms. 31,32 In conclusion, our study provides favorable data for the generalizability of the safety and efficacy of thrombectomy in the ''real-world'' setting and adds to the growing literature supporting that patients may be safely treated outside the constraints of randomized trials and strict guidelines. Other coauthors: critical revision of manuscript.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, as less than 50% of the Trevo registry patients met the inclusion criteria for previous RCTs, it represents a unique opportunity to explore new treatment paradigms. 31,32…”
Section: Discussionmentioning
confidence: 99%
“…Distal artery occlusions may present with high clinical severity and projected disability. These studies concluded that endovascular therapy for DAO may be safe 23,24 , hence the importance that the same standards of specificity and sensitivity of proximal LVO will apply on distal occlusions. Given the low sensitivity of radiologist in detecting distal vessel occlusions an AI software can be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…104 The evolution of EVT continues with several ongoing trials aiming to extend the indication of EVT, including in LVO stroke patients presenting with mild stroke severity NIHSS score <6 (ENDOLOW [Endovascular Therapy for Low NIHSS Ischemic Strokes] and MOSTE [Minor Stroke Therapy Evaluation]), large infarct burden (eg, ASPECTS <5; large core volumes on CTP/DWI: TENSION, LASTE, TESLA, SELECT-2, and RESCUE Limit), and distal arterial occlusions (DUSK, ESCAPE-MeVO, and DIS-TALS), as previous reports have demonstrated the safety and feasibility of thrombectomy in these patient populations. 51,[105][106][107][108]…”
Section: Expanding the Indications Of Endovascular Thrombectomymentioning
confidence: 99%